(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
The experimental angular distributions of differential cross-section (CS), vector analyzing power (iT11) and tensor analyzing powers (T20, T21 and T22 ) for the 12C(6Li, 6Li)12C elastic scattering at laboratory energy of 30 MeV are simultaneously analyzed in the structure of simple optical model (OM) using shallow Non-Monotonic (NM) and deep Monotonic Woods-Saxon (MWS) potentials. The Pauli-laden energy density functional (EDF) theory which results in NM potentials is also discussed. Equally good fits to the CS, T20, T21, and T22 data are obtained using both NM and MWS potentials. But iT11data is only reproduced well using NM potentials in OM. The conclusion is that the shallow NM potentials seem better than the deep MWS for simultaneous description of the CS, iT11, T20, T21 and T22 data. J. Bangladesh Acad. Sci. 48(1); 99-109: June 2024